Development and validation of questionnaire on knowledge, attitudes, practices and perceived barriers related to nutrition care process among clinical dietitians in Malaysia - Bahari, Zaini (2015)
The introduction of the Nutrition Care Process (NCP) by the American Dietetics Association (ADA) in 2003 provides a standardised framework for clinical dietitians in nutrition care delivery. It is imperative to assess the knowledge,attitudes, practices, and perceived barriers (KAPB) of the clinical dietitians on the NCP. To date, no questionnaire has been developed and validated to assess the KAPB on the NCP. Thus, the present study consisted of two phases, aimed to develop and validate the questionnaire namely Knowledge,Attitudes, Practices, and Perceived barriers on the NCP (KAPB-NCP). The Phase 1 study which was the development of the KAPB-NCP questionnaire involved the generation of 116 items related to sociodemographic characteristics (7 items), professional development (3 items),organisational culture’s support on the NCP (2 items), knowledge (27 items),attitudes (39 items), practices of the NCP (20 items), and perceived barriers to implement the NCP (14 items). A panel of eight experts who were clinical dietitians and academicians were invited to review the online version of the questionnaire. Content validity was assessed quantitatively and qualitatively using Content Validity Index (CVI) and open-ended comments. A total of 87 out of 100 items from KAPB domains showed excellent content validity (k* > .74) and 10 items showed good (k* = .60 - .74) content validity. Only three items had low CVI (k* < .40). The average CVI for all items in the questionnaire was .90. The questionnaire was finalised to consist of 72 items. The Phase 2-Step 1 study was the validation of the KAPB-NCP questionnaire established in Phase 1 using factor analysis. It involved a cross-sectional study among 100 clinical dietitians in Malaysia. The KAPB-NCP questionnaire was completed via online survey. Construct validity and reliability of the items in the questionnaire were determined through exploratory factor analysis (EFA) and internal consistency coefficient respectively. Seventy respondents completed the questionnaire, represented a response rate of 70%. EFA identified two underlying factors for attitudes (15 items), one underlying factor for practices (9 items), and two underlying factors for perceived barriers (10 items). Variance obtained for the factors in attitudes, practices, and perceived barriers was 53.56%, 44.38%, and 60.53% respectively. Internal consistency coefficients for KAPB domain were .526, .890, .872, and .880 respectively. The questionnaire was finalised to consist of 60 items. The Phase 2-Step 2 study was further validation of the KAPB-NCP questionnaire established in the Phase 2-Step 1 using inferential statistics. A cross-sectional study was conducted among 240 clinical dietitians in Malaysia. A self-administered KAPB-NCP questionnaire was completed online. Of 196 respondents who completed the questionnaire, 93.4% were female. More than two-third of the respondents (67.9%) were working in government hospitals,21.4% in private hospitals, 6.6% in university hospitals, and 4.1% in health clinics. The mean practice score was 34.65 ± 6.00. The multivariate analysis indicated five factors determine the practice of the NCP namely perceived barriers to implement the NCP (β = -.264, p = <.001), support from the head of department (β = .225, p = <.001), attitude towards the NCP (β = .244, p =.001), utilisation of the NCP at critical care area (β = .153, p = .009), and years of working (β = .132, p = .024). In conclusion, this study has established a valid and reliable questionnaire,namely KAPB-NCP to assess the KAPB on the NCP. It was appeared that the practice of the NCP was likely to be influenced by the individual dietetics professionals and their administrators. Hence, multiple strategies that take into consideration these influencing factors might offer great potential to enhance the implementation of the NCP into dietetics practice.